Characterisation of the expression of select genes in response to key marine pollutants in the triplefin Forsterygion capito - Diana Montenegro; Louis A. Tremblay; Zoë Hilton; Gavin Lear (New Zealand Journal of Marine and Freshwater Research, 2021)
Biomarkers in receptor species can be used to assess and monitor ecosystem health. This study aimed to develop mRNA biomarkers in the New Zealand triplefin Forsterygion capito and validate their induction in response to common estuarine contaminants. The targeted genes were cytochrome P450 1A ( cyp1a ), metallothionein ( mt ), vitellogenin ( vtg ), and cytochrome P450 aromatase ( cyp19b ). Fish were treated with intraperitoneal injections of benzo[a]pyrene (BaP), zinc, and 17β‐oestradiol (E 2 ). Levels of cyp1a were upregulated in the livers of fish exposed to BaP, and the vtg gene was up‐regulated in male fish exposed to E 2 . These results indicated that these two biomarkers in F. capito can be used to assess exposure to contaminants exerting similar mechanisms of toxicity.